2011
DOI: 10.1093/jnci/djq563
|View full text |Cite
|
Sign up to set email alerts
|

Novel Breast Cancer Susceptibility Locus at 9q31.2: Results of a Genome-Wide Association Study

Abstract: These findings provide further evidence on the role of genetic variation in the etiology of breast cancer. Fine mapping will be needed to identify causal variants and to determine their functional effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
125
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 33 publications
12
125
0
1
Order By: Relevance
“…Our findings with 6q25.1-rs3734805 and 6q25.1-rs9383938 are consistent with the GWAS study on breast cancer where these variants were first reported (28) and with a subsequent case-control study of 6q25.1 (55). A meta-analysis of five GWAS of MD within the Marker Of DEnsity (MODE) consortium, examined 23 of the established breast cancer variants with MD and reported a significant association of rs2046210 -ESR1 and MD (18).…”
Section: Consistency and Inconsistency Of Overall Findings With Previsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings with 6q25.1-rs3734805 and 6q25.1-rs9383938 are consistent with the GWAS study on breast cancer where these variants were first reported (28) and with a subsequent case-control study of 6q25.1 (55). A meta-analysis of five GWAS of MD within the Marker Of DEnsity (MODE) consortium, examined 23 of the established breast cancer variants with MD and reported a significant association of rs2046210 -ESR1 and MD (18).…”
Section: Consistency and Inconsistency Of Overall Findings With Previsupporting
confidence: 88%
“…Genome-wide association studies (GWAS) and candidate gene studies have identified more than 75 SNPs that may be associated with risk of breast cancer in Caucasians (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). It has been estimated that there is about a 10% overlap in the genetic factors that influence breast cancer risk and those that determine variation in MD (5).…”
Section: Introductionmentioning
confidence: 99%
“…5 Genome-wide association studies (GWAS) have identified a significant association between some genetic variants and breast cancer risk. [6][7][8][9][10] Among these variants, an intronic variant in the FGFR2 gene is currently identified as one of the most important genetic susceptibility locus in breast cancer. 10 Furthermore, several single-nucleotide polymorphisms (SNPs) in FGFR2 were confirmed to have a high correlation with breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…5 Genome-wide association studies (GWAS) have identified 14 independent common single nucleotide polymorphisms (SNPs) that show consistent associations with female breast cancer risk. [6][7][8][9][10][11][12][13] To examine whether these variants contribute to breast cancer risk after radiotherapy, we analyzed blood samples from 2 case-control series. The discovery phase comprised 449 women with HL treated with supradiaphragmatic radiotherapy in England and Wales during 1963-2003 at ages Ͻ 36 years: 140 had breast cancer after HL treatment (the "cases") and 309 had had no solid cancer after HL (the "controls").…”
Section: Introductionmentioning
confidence: 99%